Ekonomiczne uwarunkowania zmian aktywności produkcyjnej gospodarstw indywidualnych w Polsce w latach 1962 - 1976 - Czyżewski, Andrzej (Wydział Prawa i Administracji UAM, 1979)
One of the main factors of changes in the country has been indicated in this paper. It is the productive activity of individual farms. This conception, due to the factor analysis applied at work, was given a measurable form that allowed to draw a comparative analysis of the observed changes in space and time- The following years have been tested: 1962, 1972 and 1976. Ten agricultural regions (1962, 1972) and 232 rural communes (1976) are the objects of interest. These units are described in turn by the initial matrix of information formulated on the ground of 30 ad 60 features. The construction of the factor determinate for 1962 and 1972 is composed of 9 features whale it consists of 13 features for 1976. They all are characteristic relative high factor contents. A precise analysis of the distinguished structures allowed to draw some conclusions of a more general character. It was observed, among others, that the nature of the trend accepts interdependence between growth of incoime and yield of agricultural produce on the one hand and natural consomption decrease in farms on the other. It was stated that space and degree of saturation with production meaner the most important conditions of the productive activity. A lack of interdependence between the farm productive activity and expenses on dwelling-houses, flat's provision with water-supply-and-sewage system, bathrooms, radio- and TV-sets or other articles testifying a higher standard of living lead to different conclusions. It was noticed that even in farms of a relatively high productive activity the income volume was not the base of its distribution which would favour improvement of family's living standard. Separation of productive farms and hausekeeping is reflected here. The research carried out reveal other phenomena as well. One of them is lower labour productivity of the two-job population in agriculture. Some regularity was observed showing that the more people engaged in agriculture perform at the same time work outside agriculture the lower are the productive effects of farms. The second part of considerations present regional diversification of individual farm productive activity in the period under examination. In the summing up attention was drawn to agricultural policy in initiating productive activity "reserves". A marked revival of individual farms in the seventies is, among others, its result. It was mostly observed in the northern territories. Reserves situated, among others, in a better agrarian structure, relatively developed infrastructure of agriculture production and also possibilities of intensification of contacts with the nationalized sector were initiated. The data also confirm growing importance of the agricultural production in the north-east macro-region.
Economic Conditions of Productive Activity Changes in Individual Farms in the Years 1962-1976